The Role of Capital Flows in the International Transmission of US Monetary Policy: The Case of Turkey - Nuri Çağrı Akar; Cemil Varlık (Ekonomi, Politika & Finans Araştırmaları Dergisi)
This article aims to examine the impacts of US monetary policy (MP) changes on the Turkish economy and to research the transmission channels through which these effects are spillovers. A Structural Vector Autoregressive (SVAR) model is estimated for the period 2002:01–2017:12, during which a flexible exchange rate regime was adopted in the Turkish economy. According to the impulse-response analysis, the Turkish interest rate responds positively and significantly to the US Effective Federal Funds Rate (EFFR). This result shows that the Central Bank of the Republic of Turkey’s (CBRT) MP follows the FED's MP and is consistent with the dilemma hypothesis of Rey (2015). The analysis also demonstrates that both the EFFR and the VIX have a negative impact on net total capital inflows to the Turkish economy. The impulse-responses for the three components of net capital inflows indicate important conclusions. Firstly, neither EFFR nor VIX has a significant impact on Net Foreign Direct Investment (NFDI) inflows. Secondly, Net Portfolio Investments (NPI) respond significantly to the VIX but not to the EFFR. Thirdly, Net Other Investments (NOI) respond significantly to the EFFR but not to the VIX. These findings indicate that the NOI component plays a direct and major role in the emergence of the US MP’s spillover effects on the Turkish MP.